Educational mediamorphosis and constructivist paradigm - Vyšniauskas, Arūnas (Politologija, 1998)
Rapid development of novel informational technologies and the ever changing education, the author, doctor of humanitarian sciences, emphasises, makes the entries inside the Great Politics more frequent. Yearly reports, as of 1997 and 1998, by the President of the United States show that the wish of the United States to have the best educational system is tightly bound to the US Global Strategy. Author states that 'in the entire world, education becomes commercialised - it floats away from governmental institutions into the private sphere.' As a matter of fact, in the sphere of education fundamental changes, guided by achievements of cognitive sciences, occur, which have been radically transforming the dominant outlook in regard to the knowledge of the world. Thus, in the face of these processes, one of the new paradigms, namely - constructivist one - is formulated. Information revolution actualises, on the one hand, the primary meaning of the Latin word industria and, on the other - the ideas of the Enlightenment. Therefore, in this article spectrum of the aforementioned problems is analysed.Great politics and educational revolution. In the first chapter of the article the author deliberates upon the time-relevance of issue. On the first hand, he commences to introduce us to the "era of electronic democracy". Having identified active correlation and relationship between education and wider - social aspects of the individual, namely, his societal status, affirms that the theme of educational and novel informational technologies becomes one of the most important in the internal politics of Great nations. Therefore, the author proceeds: 'Politicians, who 'rediscovered' the educational theme several years ago, must not ignore these tendencies because their ignorance and lack of focus with respect to educational strategy and youth problems may cause serious internal tensions likewise it had happened thirty years ago in France and Western Germany.' Author precautions that the introduction of new technologies into the educational systems and commercialisation of it may intensify social tensions. At the moment, in the West there are few politicians who speak of the danger that the society may split into those of the working class, that is - lacking resources to finance the studies, and eventually in danger of staying unemployed, and those who, after receiving university education, can assure their prosperity. On the second hand, author notifies, that due to modern informational revolution, the education and studies change in the entire world. Although in twenty years, he says, the entire educational system will undergo dramatic changes, nobody knows what will it look like. Great nations noticing that such businessmen as Bill Gates, who declare that they bind huge perspectives to educational business, by creating their own, can demonopolise, or overlay, the government-supported educational systems, on their side, proclaim that education is an increasingly important part of national strategy. The same was uttered by the US President Bill Clinton in his 10-point plan on how the Americans must constitute their education. Core role in this plan is devoted to the role of novel technologies, computers, Internet.Novel attitude towards teaching and studying. In comparison to the first chapter, in this second chapter of the article the author elaborates upon a theoretical side of an issue concerning, from one viewpoint, the teaching and from the other - the studying. Author proceeds: cognitive sciences, which have expanded in the last decades, ground the attempts to "dive" inside the brains of human being, use computer-world concepts to define their activity and functions; likewise, they endeavor upon explaining spiritual cases (which they perceive as processes of managing the information) by using a neural-level dimension. Furthermore, the cognitive sciences refrain not from explaining objective reality. They ask: "Why not?", and explicate five (likewise Marxists, plus, considerably - materialist, constructivist) principles of teaching and studying. With respect to an intellectual aptitude of a person to construe ideas, concepts, etc., the author presents different scientific standpoints: from Swiss Jean Piaget, Durkheim, Socrates, Vico, Comenski, modern internauts; instructionists - Bransford, Brown, Collins, Swiss scientist Dubs, who in his survey presents seven key principles which characterise constructivism, a paradigm on the basis of which American universities (especially- business and medical) organise students' self-regulative studying. In the following three chapters the author, in comparison to preceding chapters, contemplates over both theoretical (methodological) and practical issues characterising the constructionist paradigm:Creative studying instead of receptive studying by explorative methodsCognitive teaching of a master and computerised educationPerspectives of new pedagogical researches
Keywords: -